Insulin treatment partially prevents cognitive and hippocampal alterations as well as glucocorticoid dysregulation in early-onset insulin-deficient diabetic rats. (July 2018) - Marissal-Arvy, Nathalie; Campas, Marie-Neige; Semont, Audrey; Ducroix-Crepy, Céline; Beauvieux, Marie-Christine; Brossaud, Julie; Corcuff, Jean-Benoit; Helbling, Jean-Christophe; Vancassel, Sylvie; Bouzier-Sore, Anne-Karine; Touyarot, Katia; Ferreira, Guillaume; et al.
Highlights: Diabetic juvenile rats displayed impaired hippocampal-dependent cognitive performances. Diabetic juvenile rats showed decreased hippocampal microstructure and neurogenesis. Hippocampal deficits were associated with an impaired regulation of glucocorticoids. Hippocampal impairments were not totally prevented by insulin treatment. Complementary interventions may prevent cerebral alterations in early-onset diabetes. Abstract: The diagnosis of Type 1 Diabetes (T1D) in ever younger children led us to question the impact of insulin deficiency or chronic hyperglycemia on cerebral development and memory performances. Here, we sought abnormalities in these traits in a model of streptozotocin-induced diabetes in juvenile rats treated or not by insulin. We made the assumption that such alterations would be related, at least in part, to excessive glucocorticoid exposition in hippocampal neurons. We have compared 3 groups of juvenile rats: controls, untreated diabetics and insulin-treated diabetics. Diabetes was induced by streptozotocin (65 mg/kg IP/day, 2 consecutive days), at postnatal days 21 and 22 and a subcutaneous pellet delivering 2 U of insulin/day was implanted in treated diabetic rats 3 days later. Three weeks after diabetes induction, cognitive performances (Y maze, object location and recognition tests), in vivo brain structure (brain volume and water diffusion by structural magnetic resonance imaging), and hippocampal neurogenesis (immunohistochemical labeling) measurements were undertaken. Corticosterone levels were evaluated in plasma under basal and stress conditions, and within hippocampus together with 11β-dehydrocorticosterone to assess 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) activity. The comparison of the three experimental groups revealed that, compared to controls, untreated diabetic rats showed decreased cognitive performances in Y-maze and object location test (p < 0.05), decreased brain and hippocampal microstructure (p < 0.05), and decreased maturation and survival of hippocampal newborn neurons (p < 0.05). These alterations were associated with increased plasma corticosterone at the baseline nadir of its secretion (p < 0.001) and during the recovery phase following a restraint stress (p < 0.001), as well as increased hippocampal corticosterone levels (p < 0.01) and 11β-HSD1 activity (p < 0.05). As untreated diabetic rats, insulin-treated diabetic rats displayed decreased brain volume and water diffusion (p < 0.05 compared to controls) and intermediate memory performances and hippocampal neurogenesis (p value not significant compared to either controls or untreated diabetics). Moreover, they were similar to controls for basal plasma and hippocampal corticosterone and 11β-HSD1 activity but show increased plasma corticosterone during the recovery phase following a restraint stress similar to untreated diabetics (p < 0.001 compared to controls). Thus, insulin did not completely prevent several hippocampal-dependent behavioral and structural alterations induced by diabetes in juvenile rats which may relate to the higher cognitive difficulties encountered in T1D children compared to non–diabetic controls. Although insulin restored basal corticosterone and 11β-HSD1 activity (in hippocampus and plasma), the negative feedback regulation of corticosterone secretion after stress was still impaired in insulin-treated diabetic rats. Further characterization of insulin control on glucocorticoid regulation and availability within hippocampus is awaited.